Dynamics of a gravity car race with application to the Pinewood Derby - B. P. Mann; M. M. Gibbs; S. M. Sah (Mechanical Sciences, 2012)
This paper investigates the underlying physics of a gravity car race. This work seeks to provide a sound theoretical basis to elucidate the design considerations that maximize performance while simultaneously dispelling false assertions that may arise from incomplete analyses. The governing equations are derived and solved analytically to predict race times; trend analyses are then performed along with a sensitivity analysis to ascertain the most important factors that influence performance. The inferences from a conservative energy balance are then compared with the predictions from the full set of differential equations, which include the dissipative terms associated with air resistance and friction.